A blockchain-based concept for generating asset-related services for supply chain events based on on- and off-chain data - Schmidt, Felix Hilmar Michael (Stellenbosch : Stellenbosch University, 2025)

(untitled)
Schmidt, F. 2025. A Blockchain-based Concept for Generating Asset-related Services for Supply Chain Events Based on on- and off-chain Data. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/e766c97c-7a9b-4510-ab39-034c5861bca1